New Sunday Times, 26 April 2009 - K. M. Boopathy (The New Straits Times Press (M) Bhd, 2009)
Malaysi's goal of reaching the Sudirman Cup semi-finals for the first time is well within reach if the draw in Guangzhou yesterday was any indication as the fourth seeds have avoided being drawn in the same group with holders China and second seeds Indonesia.